Pengujian Antibakteri Ekstrak Etanol Daun Bunga Lilin (Pachystachys Lutea L.) Terhadap Bakteri Staphylococcus Aureus Atcc 1055 Dan Escherichia Coli Atcc 25922 - Kartikawati, Endah; Slamet , Tuty; Pulungan, Habiba Fikri Farika; Yuni , Mutiara Khairati (BORNEO JOURNAL OF PHARMASCIENTECH, 2025)
Staphylococcus aureus and Escherichia coli are two pathogenic bacteria that often cause infections in humans. In efforts to combat various infections caused by pathogenic bacteria, the use of medicinal plants as alternative treatments is gaining increasing attention. One such plant is the Candle Flower (Pachystachys lutea L). This study was conducted to identify the antibacterial activity of Candle Flower leaf extract (Pachystachys lutea L) against Staphylococcus aureus and Escherichia coli using the disk diffusion method. The results showed antibacterial activity against Staphylococcus aureus, forming clear zones at concentrations of 6.25%, 12.5%, 25%, and 50%, measuring 6.00, 6.93, 8.06, and 10.81 mm, respectively. Meanwhile, the antibacterial activity against Escherichia coli formed clear zones at concentrations of 6.25%, 12.5%, 25%, and 50%, measuring 8.10, 8.52, 9.72, and 12.35 mm, respectively. The ethanol extract of Candle Flower leaves (Pachystachys lutea L.) can inhibit the growth of Staphylococcus aureus ATCC 1055, with the best concentration being 50%, forming a clear zone diameter of 10.56 mm, and against Escherichia coli, with the best concentration being 50%, forming a clear zone diameter of 12.35 mm. The clear zones formed fall into the criteria of strong inhibition zones.